Analysis of microleakage of temporary restorative materials in primary teeth - Geórgia Linhares dos Santos; Ana Paula Caldeira de Andrada Beltrame; Thaísa Cezária Triches; Marcos Ximenes-Filho; Daniel Baptista; Michele Bolan (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of this study was to compare the coronal microleakage of restorative materials used between sessions of endodontic treatment in primary teeth. Materials and Methods: Forty healthy primary canines were chosen and randomly allocated to four groups: Group 1 - Cimpat Branco ® (n = 10), Group 2 - Bioplic ® (n = 10), Group 3 - Maxxion R ® glass ionomer cement (n = 10), and Group 4 (control) - Z350 ® composite resin (n = 10). Class V cavities were created and fillings carried out following the manufacturer's instructions. The teeth were submitted to thermocycling, sealed, and immersed in 0.5% basic fuchsin solution for 24 h. The teeth were split along their long axis in the vestibulolingual direction and the tooth-restorative material interface was photographed. The percentage of microleakage was calculated using the ImageJ program. Data were analyzed using the analysis of variance (ANOVA) F-test and Bonferroni's t-test, with a 5% level of significance. Results: The following mean percentages of microleakage were found: Group 1 = 16.08%, Group 2 = 46.98%, Group 3 = 47.93%, and Group 4 = 11.03%. Statistically, significant differences were found in the comparison of Groups 1 and 4 to Groups 2 and 3. Conclusion: Cimpat Branco ® had a lower percentage of microleakage in comparison to Bioplic ® and Maxxion R ® glass ionomer cement.